Natural Resource as Carbon Absorbent in Industrial Activities - Segaran, Pravin (Penerbit Universiti Malaysia Perlis, 2011)
Carbon dioxide (CO2) emissions have increased in recent years in the cities of developing countries, due to heavy traffic and low quality fuel. Concentrations in the atmosphere have exceeded the safe limits of 350 ppm since 1988. There is now a general acceptance that increased efforts must be made to reduce industrial sources of this greenhouse gas. In order to test if a significant proportion of carbon could be absorbed by mineral soil, a study was carried out. Therefore this study will investigate the potential of natural resource carbonation using tropical mineral soil to study the capacity of this natural resource to capture carbon dioxide. The carbonation process will be carried out in a fabricated, laboratory-sized reactor to perform an accelerated carbonation by using different mixing speed, temperature, pH adjustment, contact time, gas flow rate, and particle size. The expected outcome from this research is to prove that the tropical mineral soil could enhance the CO2 uptake in the carbonation process. The soils are reacted in a slurry form with flowing carbon dioxide, at different temperatures and parameters. The outcome has found upto 64 percentage removal of carbon dioxide from the stream, and proves a viable method for air pollution remediation.